Employment and the youth mental health crisis in Canada: distinct influences across phases of the school-to-work transition - Dupéré, Véronique; Caron-Diotte, Mathieu; Beauregard, Nancy; Courdi, Clémentine; Ahn, Jiseul Sophia; Olivier, Elizabeth; Tardif-Grenier, Kristel; Litalien, David (Frontiers in Public Health, 2025)
ObjectivesEmployment-related challenges and uncertainties are thought to contribute to the mental health crisis affecting young adults globally. Yet, few studies have examined how employment characteristics relate to young adults’ mental health. This study addresses this gap, considering how the role of employment might vary depending on young adults’ educational status and level.MethodsA representative sample of 6,700 young adults (18–30 y.o.) drawn from Statistics Canada’s Longitudinal and International Study of Adults (2012–2020) was used to examine links between working hours and employment in a study-related job and mental health (life satisfaction, global mental health, psychological distress), beyond prior mental health and background characteristics. Interactions with student status were also incorporated.ResultsAmong young adults in tertiary (university, college) education, mental health worsened as working hours increased. For all other participants, the opposite was observed: working more hours was associated with improved mental health. Overall, the best outcomes were observed among tertiary-enrolled students not working, and the worst among youth neither working nor in education. The size of the differences between these groups were non-negligible (with d ranging between 0.37 and 0.47). Across all groups, employment in a study-related job was marginally associated with higher life satisfaction (but not with psychological distress or global mental health).ConclusionWorking hours contribute to young adults’ mental health in contrasting ways, depending on their position on the school-to-work transition continuum. Enhancing young adults’ access to meaningful employment in study-related jobs with an adapted schedule could help mitigate the youth mental health crisis.